2022
DOI: 10.3389/fimmu.2022.949423
|View full text |Cite
|
Sign up to set email alerts
|

Divide and Conquer: Phenotypic and Temporal Heterogeneity Within CD8+ T Cell Responses

Abstract: The advent of technologies that can characterize the phenotypes, functions and fates of individual cells has revealed extensive and often unexpected levels of diversity between cells that are nominally of the same subset. CD8+ T cells, also known as cytotoxic T lymphocytes (CTLs), are no exception. Investigations of individual CD8+ T cells both in vitro and in vivo have highlighted the heterogeneity of cellular responses at the levels of activation, differentiation and function. This review takes a broad persp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 156 publications
0
12
0
Order By: Relevance
“…Lineage tracing studies have previously identified diversity in the expansion and differentiation of single T cells through primary and recall responses (Buchholz et al, 2016). Cellular heterogeneity may also contribute to the dynamic nature of adaptive immune responses to respond to a breadth of antigens (Richard, 2022; Wong and Germain, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lineage tracing studies have previously identified diversity in the expansion and differentiation of single T cells through primary and recall responses (Buchholz et al, 2016). Cellular heterogeneity may also contribute to the dynamic nature of adaptive immune responses to respond to a breadth of antigens (Richard, 2022; Wong and Germain, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the accumulation of varying levels of TCR signaling in naive T cells in the steady state can influence changes in T cell gene expression. This feature of tonic TCR signaling also raises the possibility that variable gene expression patterns in response to tonic TCR signaling result in functional heterogeneity within the naive T cell population (Eggert and Au-Yeung, 2021; Richard, 2022). This concept is consistent with models proposing that T cell responsiveness depends on previously experienced TCR signals (Huseby and Teixeiro, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…CD8+ T cells play critical roles in adaptive immunity. Antigen stimulation drives naïve CD8+ T cells to rapidly undergo a step-by-step process of early activation, clonal expansion and differentiation ( 62 65 ). In addition to early activation, IRF4 participates in the entire process of differentiation and function of effector CD8+ T cells ( 66 , 67 ).…”
Section: Effect Of Irf4 On the Differentiation And Function Of Cd8+ T...mentioning
confidence: 99%
“…Next, IRF4 combined with AP1 family TFs form an activating IRF4/AP1 complex, which integrates TCR and costimulatory signals to induce the production of a series of effector cytokines. After antigen clearance, the expression of IRF4 decreased, followed by an increase in expression of stemness-like gene T cell factor 7 ( Tcf7 ; encoding TCF1) ( Figure 3B ), and further producing memory precursor cells (MPECs) and TCF1+ memory-like T cells to rapidly function in the secondary response ( 64 , 65 ) ( Figure 3A ).…”
Section: Effect Of Irf4 On the Differentiation And Function Of Cd8+ T...mentioning
confidence: 99%
“…However, tonic TCR signals can alter chromatin accessibility and influence the expression of several genes at the transcriptional or the protein level in T cells (6)(7)(8)(9). This feature of tonic TCR signaling also raises the possibility that variable gene expression patterns in response to tonic TCR signaling result in functional heterogeneity within the naive T cell population (10,11). How the intensity of tonic TCR signals helps shape the responsiveness of naive T cells to subsequent foreign antigen stimulation remains unresolved (3).…”
Section: Introductionmentioning
confidence: 99%